The role of microbial biofilms in prosthetic joint infections - Gbejuade, Herbert O; Lovering, Andrew M; Webb, Jason C (Acta orthopaedica, 2015)
Abstract - Prosthetic joint infection (PJI) still remains a significant problem. In line with the forecasted rise in joint replacement procedures, the number of cases of PJI is also anticipated to rise. The formation of biofilm by causative pathogens is central to the occurrence and the recalcitrance of PJI. The subject of microbial biofilms is receiving increasing attention, probably as a result of the wide acknowledgement of the ubiquity of biofilms in the natural, industrial, and clinical contexts, as well as the notorious difficulty in eradicating them. In this review, we discuss the pertinent issues surrounding PJI and the challenges posed by biofilms regarding diagnosis and treatment. In addition, we discuss novel strategies of prevention and treatment of biofilm-related PJI.